Analisis penerimaan retribusi obyek pariwisata di Kota Jambi - Ahmad Sobrowi; Muhammad Safri; Erni Achmad (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
This study aims to: 1) determine the development of lavies received on tourism object, the number of tourist visits, the number of hotels and the number of tourist attractions in Jambi City, 2) to analyze the effect of the number of tourist visits, the number of hotels and the number of tourist attractions on the receipt of levies for tourism object in Jambi City. The data used in this research was secondary data. The data analysis method used in this research is the developments formula and multiple linear regression analysis with the eviews program. The results showed that realization of levies received aon tourism object in Jambi City increased by an average 0f 35.31% with an average amount of tourist visits of 55.74%, the number of hotels an average 0.50%, and the number of tourist attractions an average 0,37%. While the result of the t-test shows that partially the number of tourist visits and the number of hotels have a significant effect on the acceptance of tourism object fees in Jambi City with a significant value of P <0.05. Keywords: Receipt of tourism object retribution, Number of tourist visits, Number of hotels, Number of tourism objects